PRILAKU KONSUMEN DALAM ISLAM (Kajian Prinsip-prinsip Konsumsi dalam Perspektif Ekonomi Mikro Islam) - Siswadi, Siswadi; ‘Ainun Najihah, Wilda (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
Consumption activities or efforts to fulfill the needs that humans want, one of which must make a sacrifice by giving up something of value or value with something that they want. In other words, there are many activities that we carry out, including those that we often do, commonly called buying and selling. Islam sees the concept of buying and selling as a tool to make people more mature in their way of thinking and carrying out various economic activities. This research aims to answer, describe and analyze the research problem formulation which consists of: 1) What are the objects of consumption, (2) What are the consumer behavior assumptions?, (3) What are the principles of consumer behavior, (4) Consumer satisfaction criteria The research method used in this research is the literacy study or library research method. Literacy studies are written summaries of articles from journals, books and other documents that describe theories and information both past and present, organizing literature into the required topics and documents. The results of this research concluded that: Consumption is not just an activity of eating or drinking, but is an activity of using goods or services that can directly satisfy individual human needs. Thus, consumption can be concluded as an activity to fulfill needs in order to achieve satisfaction. Assumptions. Consumption must prioritize aspects of morality and social responsibility. Consumption is controlled by at least five principles, namely: Justice, cleanliness, simplicity, generosity and morality. Factors that influence satisfaction. Consumer: Product, service, emotional, cost and price.